Location via proxy:   [ UP ]  
[Report a bug]   [Manage cookies]                

Formulas

Download as pdf or txt
Download as pdf or txt
You are on page 1of 2

lim f (x)

x→a

f (x + h) − f (x)
h
f (z) − f (x)
z−x
 x
f (t) dt
a

 b 
n
f (x) dx = lim f (x∗i )∆xi
a max ∆xi →0
i=1


n
f (xi )∆x
i=1

f (b) − f (a)
f  (c) =
b−a

f (b) − f (a) f  (c)


= 
g(b) − g(a) g (c)

d
f (g(x)) = f  (g(x))g (x)
dx
f (x) f  (x)
lim = lim 
x→a g(x) x→a g (x)

 b  g(b)

f (g(x))g (x) dx = f (u) du
a g(a)

 x
d
f (t) dt = f (x)
dx a

6x2 − 1 x tan(x)
+
7 sin(x2 ) + cos(x3 + 1)

1

f (x, y) ds
C

 b h(x)
f (x, y) dy dx
a g(x)

f (b) − f (a) f (a + h) − f (a)


f  (a) = lim = lim
b→a b−a h→0 h

For all  > 0, there exists an N() such that |an − L| <  if n > N()

 1 

f (x) dx = lim− (1 − q) f (q n )q n
0 q→1
n=0

You might also like